INCIDENT OF THE YEAR 2010 AND LIVING KYRGYZ IN UZBEKISTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
The article is devoted to the study of Kyrgyz people in Uzbekistan in recent years.Interethnic relations, multinational policy in Uzbekistan after the collapse of the USSR,theirimpact on the Kyrgyz people in this country and demographic situation are analyzed. The situationof the Kyrgyz people of Uzbekistan during the Osh events of 2010 in Kyrgyzstan, their relationswith neighboring ethnic groups and the state’s policy in this direction were also studied.
Keywords: kyrgyz in Uzbekistan, interethnic relations, interethnic politics, Osh events.